Applicability of Emergent Pedagogies to E-Learning - Mora-Vicarioli, Francisco (2019)
This article is the result of the interest in making a current contribution to the topic of emerging pedagogies and their applicability to the context of e-learning. The term “emergent” does not have to do with a new pedagogy, but with one that adapts to the potential offered by information and communication technologies (ICT´s) for academic processes. At the methodological level, for this research, a documentary analysis was carried out in more than 60 academic sources, which had, at first, the purpose of obtaining the categories that are involved in emerging pedagogies, in order to facilitate the hermeneutical process, after this an exhaustive search was made of exponents about the different topics involved in emerging pedagogies: ubiquitous learning, educational personalism, collaborative learning, contextual or situated learning and evaluating to learn. We sought to contribute to the knowledge of the subject and in particular to the role that the teacher should assume and possible challenges that are faced through emerging pedagogies, in which skills in the management of ICT and pedagogical mediation are highlighted as key elements, in addition to promoting an active role in the students.